Supplier Evasion of a Buyer’s Audit: Implications for Motivating Supplier Social and Environmental Responsibility - Plambeck, Erica L.; Taylor, Terry A. (Manufacturing and Service Operations Management, 2016)
Prominent buyers’ brands have been damaged because their suppliers caused major harm to workers or the environment, e.g., through a deadly factory fire or release of toxic chemicals. How can buyers motivate suppliers to exert greater care to prevent such harm? This paper characterizes a “backfiring condition” under which actions taken by prominent buyers (increasing auditing, publicizing negative audit reports, providing loans to suppliers) motivate a supplier to exert greater effort to pass the buyer’s audit by hiding information and less care to prevent harm. Intuitively appealing actions for a buyer (penalizing a supplier for harming workers or the environment, or for trying to deceive an auditor) may be similarly counterproductive. Contrary to conventional wisdom, squeezing a supplier’s margin (by reducing the price paid to the supplier or increasing wages for workers) motivates the supplier to exert greater care to prevent harm—under the backfiring condition. Whereas the necessary and sufficient condition depends on the relative convexity of the supplier’s hiding cost function, a simple sufficient condition is that the supplier is likely to successfully hide information from the auditor, in equilibrium. Anecdotal evidence suggests that the backfiring condition is prevalent or becoming increasingly so. Similar insights apply to mitigation of unauthorized subcontracting.